2021
DOI: 10.1002/jlb.3mr0321-545rr
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesenchymal stromal cell-derived extracellular vesicles in acute respiratory distress syndrome (ARDS): Current understanding and future perspectives

Abstract: Acute respiratory distress syndrome (ARDS) is a devastating and life‐threatening syndrome that results in high morbidity and mortality. Current pharmacologic treatments and mechanical ventilation have limited value in targeting the underlying pathophysiology of ARDS. Mesenchymal stromal cells (MSCs) have shown potent therapeutic advantages in experimental and clinical trials through direct cell‐to‐cell interaction and paracrine signaling. However, safety concerns and the indeterminate effects of MSCs have resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 96 publications
(159 reference statements)
0
7
0
1
Order By: Relevance
“…Mesenchymal stem cells are universally renowned for their unique immunomodulatory properties; once led into circulation, they are able to reach inflammation sites ( Kallmeyer and Pepper, 2015 ), where they exert an inhibitory function on neutrophils, monocytes, dendritic cells, NK, B and T lymphocytes ( Elgaz et al, 2019 ; Juárez-Navarro et al, 2020 ; Kim H. et al, 2020 ; Moradinasab et al, 2021 ). MSC ruled immunomodulation is performed by direct cell–cell interaction (through the expression of molecules like B7H1, PD-L1, and PD-L2) ( Elgaz et al, 2019 ; Lin et al, 2020 ) as well as by a paracrine action, mediated by vehiculation of anti-inflammatory mediators through extracellular vesicles ( Schulman et al, 2018 ; Martin-Rufino et al, 2019 ; Gowen et al, 2020 ; Juárez-Navarro et al, 2020 ; Kim H. et al, 2020 ; Lin et al, 2020 ; O’Driscoll, 2020 ; Wang J. et al, 2020 ; Gentile, 2021 ; Raghav et al, 2021 ; Su et al, 2021 ) and by cytokine (IL-10, transforming growth factor-β, TNF-stimulated gene 6 protein, IFN-γ) and soluble factor indoleamine-pyrrole 2,3-dioxygenase, prostaglandinE2, nitric oxide) secretion ( Schulman et al, 2018 ; Elgaz et al, 2019 ; Martin-Rufino et al, 2019 ; Juárez-Navarro et al, 2020 ; Lin et al, 2020 ; Shetty, 2020 ; Gentile, 2021 ; Raghav et al, 2021 ). MSC polarization toward an anti-inflammatory phenotype is exacerbated by TLR stimulation elicited by pathogen components, like viral RNA ( Waterman et al, 2010 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells are universally renowned for their unique immunomodulatory properties; once led into circulation, they are able to reach inflammation sites ( Kallmeyer and Pepper, 2015 ), where they exert an inhibitory function on neutrophils, monocytes, dendritic cells, NK, B and T lymphocytes ( Elgaz et al, 2019 ; Juárez-Navarro et al, 2020 ; Kim H. et al, 2020 ; Moradinasab et al, 2021 ). MSC ruled immunomodulation is performed by direct cell–cell interaction (through the expression of molecules like B7H1, PD-L1, and PD-L2) ( Elgaz et al, 2019 ; Lin et al, 2020 ) as well as by a paracrine action, mediated by vehiculation of anti-inflammatory mediators through extracellular vesicles ( Schulman et al, 2018 ; Martin-Rufino et al, 2019 ; Gowen et al, 2020 ; Juárez-Navarro et al, 2020 ; Kim H. et al, 2020 ; Lin et al, 2020 ; O’Driscoll, 2020 ; Wang J. et al, 2020 ; Gentile, 2021 ; Raghav et al, 2021 ; Su et al, 2021 ) and by cytokine (IL-10, transforming growth factor-β, TNF-stimulated gene 6 protein, IFN-γ) and soluble factor indoleamine-pyrrole 2,3-dioxygenase, prostaglandinE2, nitric oxide) secretion ( Schulman et al, 2018 ; Elgaz et al, 2019 ; Martin-Rufino et al, 2019 ; Juárez-Navarro et al, 2020 ; Lin et al, 2020 ; Shetty, 2020 ; Gentile, 2021 ; Raghav et al, 2021 ). MSC polarization toward an anti-inflammatory phenotype is exacerbated by TLR stimulation elicited by pathogen components, like viral RNA ( Waterman et al, 2010 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
“…As suggested by successful MSC use in a number of pathological scenarios involving uncontrolled immune activation with consequent tissue damage, like for example H9N2 induced acute lung injury, ARDS, autoimmune diseases and graft-versus-host disease ( Waterman et al, 2010 ; Elgaz et al, 2019 ; Coelho et al, 2020 ; Yen et al, 2020 ; Barros et al, 2021 ; Musial and Gorska-Ponikowska, 2021 ; Su et al, 2021 ), the undeniable immunomodulatory and inflammation relieving properties of MSCs make them putative candidates as rejuvenating factors for the older immune system, on the basis of the documented ability to reduce pro-inflammatory mediators and to promote the expansion of regulatory lymphocyte subsets ( Yeo et al, 2021 ). Also, MSC transplantation can contribute to the amelioration of aging frailty ( Schulman et al, 2018 ; Florea et al, 2019 ; Sun et al, 2019 ), but MSC may exhibit age related deteriorating functions linked to inflammageing, especially in terms of alterations in number and characteristics of extracellular vesicles, DAMP production, excessive IL-6 release, loss of MSC ability to shift monocyte polarization toward M2, and triggering of ineffective hemopoiesis ( Tsuruhara et al, 2017 ; Lee and Yu, 2020 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
“…EVs derived from bone marrow stromal cells (BMSCs) accomplish antibacterial effects through enhancing the phagocytosis of bacterial monocytes to some extent ( Alcayaga-Miranda et al., 2017 ). MSC-EVs have been proven to have therapeutic benefits for ARDS and severe pneumonia in reducing acute inflammation, promoting alveolar epithelial regeneration and lung endothelial cell repair ( Shah et al., 2019 ; Su et al., 2021 ). Repairing injured alveolar epithelial cells is an effective therapeutic strategy to alleviate sepsis-induced ARDS ( Bao et al., 2015 ).…”
Section: Clinical Application Of Ev In Sepsis/ardsmentioning
confidence: 99%
“…MSC-EVs can transfer keratinocyte growth factor (KGF) mRNA to alveolar epithelial cells, thereby restore lung proteins permeability and reduce alveolar inflammation ( Zhu et al., 2014 ). Clinical trials have shown that MSCs and MSC-EVs can inhibit the secretion of pro-inflammatory cytokines and the accumulation of immune cells in the lungs of patients infected with COVID-19 ( Su et al., 2021 ).…”
Section: Clinical Application Of Ev In Sepsis/ardsmentioning
confidence: 99%
“…The therapeutic strategy is mainly based on the use of corticosteroids, hydroxychloroquine, azithromycin, and supportive care; however, the efficacy is of these methods is variable. The role of MSCs as a state-of-the-art treatment has been proposed in clinical and preclinical studies [ 4 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%